Aktivitas Antioksidan Minuman Herbal Rambut Jagung Dengan Variasi Kondisi Dan Lama Perebusan - Ismiati, Erna Retno, Dr. Nanik Suhartatik, S.TP., M.P (2015)
Herbal drink was a beverage derived from natural materials that are beneficial to the body. Herbal drink made from herbs or parts of plants. Corn silk was a one material that can be used as herbal drinks because contain antioxidant compounds. This study aims to determine the effect of corn silk condition and the boiling timefor antioxidant activity using DPPH and FRAP method, organoleptic properties and acceptability on corn silk herbal drinks. DPPH method for capturing free radicals and FRAP to capture heavy metals (Fe). The study design using RAL 2 factors with 3 repetitions analysis. The first factor was corn silk condition, the fresh corn silk (A1), dried corn silk (A2) and the second factor was time boiling, boiling 5 min (B1), boiling 10 min (B2), boiling 15 min (B3), and boiling 20 min (B4). The results showed that corn silk circumstances not affect antioxidant activity both (DPPH and FRAP), organoleptic properties, and public acceptance. Factors affecting the time boiling antioxidant activity using DPPH and color of corn silk herbal drink. The highest yield was obtained in the treatment of A1B1 which has antioxidant activity 59.404% and the FRAP value 99.088%. All treatments showed the same flavor and taste is sweet enough and prefer by the customer.